Patient-reported outcomes of zirconia dental implants: a systematic review and future directions - Behrouz Arefnia; Omid Fakheran; Norbert Jakse; Michael Payer (Journal of Patient-Reported Outcomes)
Abstract Purpose Zirconia dental implants show excellent biocompatibility and tissue integration, low affinity for plaque, and favorable biomechanical properties. However, these objective measures do not adequately replicate the patient’s perception. This systematic review evaluated the evidence on patient-reported outcome (PROs) in zirconia dental implant treatment. Methods A systematic literature review was conducted following the PRISMA guidelines, utilizing six electronic databases, and supplemented by a manual search of relevant journals and websites to ensure a thorough and comprehensive screening process. The identified studies were subjected to preidentified inclusion criteria. Only controlled clinical trials published in English were considered without limitations on the year of publication. Data on the study characteristics (follow-up, survival rate (%), implant system, number of implants, and type of treatment), PROMs, level of evidence, and Methodological Index for Nonrandomized Studies (MINORS) Bias Score were extracted. Results The initial database and hand search yielded 596 articles; 189 were included in the title and abstract screening after excluding the duplicates. Eighteen articles were selected based on the inclusion criteria, among which six were excluded because they did not match the research question. Thus, the final selection comprised 12 articles. Most PROMs (aesthetics, speaking, comfort, chewing ability, and general satisfaction) at prosthetic delivery revealed significantly improved average scores than those at pretreatment. Conclusions Despite the respective limitations of the articles included in this systematic review, patients revealed high satisfaction levels with regard to zirconia dental implants. A high level of heterogeneity was observed among the instruments used for measuring the patient-reported outcomes in patients with zirconia implants, thus highlighting the need to develop specific PROMs in the future.